Role of pharmacogenomics in T-cell hypersensitivity drug reactions. Issue 4 (August 2021) - Hertzman, Rebecca J.; Deshpande, Pooja; Gibson, Andrew; Phillips, Elizabeth J.
Abstract : Purpose of review: An update of the pharmacogenetic risk factors associated with T-cell-mediated delayed hypersensitivity reactions. Recent findings: Recent HLA associations relevant to our understanding of immunopathogenesis and clinical practice include HLA-B * 13:01 with co-trimoxazole-induced SCAR, and HLA-A * 32:01 with vancomycin-DRESS, for which an extended HLA class II haplotype is implicated in glycopeptide antibiotic cross-reactivity. Hypoactive variants of ERAP1, an enzyme-trimming peptide prior to HLA loading, are now associated with protection from abacavir-hypersensitivity in HLA-B * 57:01+ patients, and single-cell sequencing has defined the skin-restricted expansion of a single, public and drug-reactive dominant TCR across patients with HLA-B * 15:02-restricted carbamazepine-induced SJS/TEN. More recent strategies for the use of HLA and other risk factors may include risk-stratification, early diagnosis, and diagnosis in addition to screening. Summary: HLA is necessary but insufficient as a risk factor for the development of most T-cell-mediated reactions. Newly emerged genetic and ecological risk factors, combined with HLA-restricted response, align with underlying immunopathogenesis and drive towards enhanced strategies to improve positive-predictive and negative-predictive values. With large population-matched cohorts, genetic studies typically focus on populations that have been readily accessible to research studies, but it is now imperative to address similar risk in globally relevant and understudied populations.